Real-time trajectory imaging of alpha particles emitted from actinium-225 and its daughter radionuclides - Seiichi Yamamoto; Masao Yoshino; Kenji Shirasaki; Kohei Nakanishi; Kei Kamada; Akira Yoshikawa; Jun Kataoka (Scientific Reports)
Abstract In targeted alpha-particle therapy, actinium-225 (Ac-225) has emerged as a radionuclide of potential, driving extensive efforts to develop innovative radiopharmaceuticals. High-resolution imaging of alpha particles is required for precisely detecting alpha-emitting radionuclides in cellular environments and small organs. Here, we report real-time trajectory imaging of alpha particles emitted by Ac-225 and its daughter radionuclides, utilizing an alpha particle trajectory imaging system. This system incorporates a magnification unit, a cooled electron-multiplying charge-coupled device (EM-CCD) camera, and a Ce-doped Gd3Al2Ga3O12 (GAGG) scintillator. Alpha particles were projected onto the GAGG scintillator, producing magnified images that were captured at 100 ms intervals. We successfully tracked particle trajectories with varying lengths and intensities for 4 different alpha particles emitted from Ac-225 and its daughter radionuclides with a spatial resolution of 1.0 μm. Notably, we achieved the imaging of sequentially emitted trajectories from Fr-221 and its decay product At-217, characterized by short decay intervals, along with the extended trajectories of high-energy alpha particles emitted by Po-213. These results demonstrate that high-resolution trajectory imaging, integrated with temporal and energy information, offers profound insights into the real-time behavior of Ac-225 and its daughter radionuclides within living cells or tissue sections, thereby driving advancements in targeted alpha-particle therapy.